Faktor Determinan Struktur Modal Perusahaan Manufaktur Yang Listing Di Bei (Studi Pada Perusahaan Manufaktur Sektor Barang Konsumsi Di Bei Periode 2016-2018) - Wahyudi Kurniawan; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstracThis research was conducted with the aim to analyze the effect of Profitability (NPM), Asset Structure and company growth on the company's capital structure. The population used in this study is manufacturing goods sector manufacturing companies listed on the Indonesia Stock Exchange in the period 2016-2018. The sample used in this study was purposive sampling technique. Companies included in the study criteria consisted of 23 companies during the 3-year study period. The data collection method used in this study is the documentation of the financial statements of the manufacturing companies in the consumer goods sector which are listed on the IDX. The analysis used is multiple linear regression by testing the hypothesis using the t test.The results of the study explained that the profitability variable by using Net Profit Margin (NPM) had no effect on the company's capital structure and the asset structure had no effect on the company's capital structure and the company's growth had no effect on the company's capital structure.Keywords : profitability, asset structure and company growth